Variation in GP decisions on antihypertensive treatment in oldest-old and frail individuals across 29 countries - Streit, Sven; Verschoor, Marjolein; Rodondi, Nicolas; Bonfim, Daiana; Burman, Robert A; Collins, Claire; Gerasimovska Kitanovska Biljana; Gintere, Sandra; Gómez Bravo, Raquel; Hoffmann, Kathryn; Iftode, Claudia; Johansen, Kasper L; et al. (BMC Part of Springer Nature, 2017)
In oldest-old patients (>80), few trials showed efficacy of treating hypertension and they included mostly the healthiest elderly. The resulting lack of knowledge has led to inconsistent guidelines, mainly based on systolic blood pressure (SBP), cardiovascular disease (CVD) but not on frailty despite the high prevalence in oldest-old. This may lead to variation how General Practitioners (GPs) treat hypertension. Our aim was to investigate treatment variation of GPs in oldest-olds across countries and to identify the role of frailty in that decision.